Blowing on the Hot Food Increasing Bacteria Contamination - Fathimah Fathimah; Lia Mustika; Inma Yunita Setyorini (University of Darussalam Gontor, 2021)
Blowing hot food and drinks is a culture in society that can cause food contamination with microorganisms. This study aims to determine the difference between the level of microorganism contamination in hot blown and unblown food. This study used a completely randomized design experimental method with blown and non-blown treatments. Each treatment was made twice. The calculation of the level of contamination is calculated by calculating the total number of colonies using the Coloni counter. The results showed that there was a significant difference (p = 0.001) between the samples that were blown (130 colonies 12 hours, 134 colonies 24 hours) and not blown (13 colonies 12 hours & 21 colonies 24 hours), the number of bacterial contamination in the blown samples was more larger than the unblown sample. Conclusion: there is a significant difference in the number of microorganisms between blown and non-blown